Strengthening Digital Literacy for Citizenship Education Students Through Articulate Storyline-Based Interactive Media - Kurnisar Kurnisar; Mariyani Mariyani; Camellia Camellia; M. Alif Al Ghifari; Meydria Meydria (JED (Jurnal Etika Demokrasi), 2022)
Media literacy in the era of the digital revolution has become an important issue in various fields. One of them is through learning designs by teachers to hone the abilities of teachers and students wisely in using technology-based media that already exist today. This study aims to find out how to strengthen student media literacy through testing of multimedia products based on articulate storylines in the PPKn FKIP Unsri study program. This research is a type of research and development (Research and Development) which refers to the R D Cycle Borg and Gall which has been modified into three stages, namely preliminary studies, product development and product trials. This research is the result of which was carried out at the product development stage, namely the product trial stage (product validation, trial and potential impact). Data collection techniques through questionnaires/questionnaires and tests. The respondents were students and media expert validators. The results of the media expert validation test can be concluded that the multimedia articulate storyline is already valid with a feasibility test with an average value of 92.1%. While the results of the one to one trial, it was found that the articulate storyline-based interactive media was good with a questionnaire percentage of 88.5%, the small group found that the articulate storyline-based interactive media was good with 85% questionnaire percentage and the field test concluded that it was obtained percentage of 88.3%. This shows that at the stage of developing this interactive media product, it has met the criteria for a good product. Furthermore, a test was conducted to see the potential impact of the data obtained from the pretest and posttest values above, so that N gain was 0.54 which means that the potential impact of developing this articulate storyline-based multimedia is moderate.Literasi media di era revolusi digital menjadi isu penting oleh berbagai bidang. Salah satunya melalui desain pembelajaran oleh pengajar untuk mengasah kemampuan pengajar dan mahasiswa secara bijak dalam menggunakan media berbasis teknologi yang telah ada saat ini. Penelitian ini bertujuan untuk mengetahui bagaimana penguatan literasi media mahasiswa melalui uji coba produk multimedia berbasis articulate storyline di prodi PPKn FKIP Unsri. Penelitian ini merupakan jenis penelitian dan pengembangan (Reearch and Development) yang mengacu pada R D Cycle Borg and Gall yang telah di modifikasi menjadi tiga tahap yaitu studi pendahuluan, pengembangan produk dan uji coba produk. Penelitian ini ialah hasil yang dilaksanakan pada tahap pengembangan produk yaitu tahap uji coba produk (validasi produk, uji coba dan dampak potensial). Teknik pengumpulan data melalui angket/kuesioner dan tes. Yang menjadi responden ialah mahasiswa dan validator ahli media. Hasil uji validasi ahli media dapat disimpulkan bahwa multimedia articulate storyline ini sudah valid dengan adanya uji kelayakan dengan nilai rata-rata 92,1%. Sedangkan hasil uji coba one to one  didapatkan bahwa media interaktif berbasis articulate storyline tersebut sudah baik dengan persentase angket 88,5%, small group  didapatkan bahwa media interaktif berbasis articulate storyline tersebut sudah baik dengan persentase angket 85%  dan  field test diperoleh simpulan bahwa  maka diperoleh persentase sebesar 88,3%.  Hal ini menunjukkan bahwa pada tahap pengembangan produk media interaktif ini telah memenuhi kriteria produk baik. Selanjutnya dilakukan tes untuk melihat dampak potensial diperoleh data nilai pretest dan posttest di atas maka didapatkan N gain 0,54  yang bermakna dampak potensial pengembangan multimedia berbasis articulate storyline ini sedang.